Impact of TNF-α Inhibitors on Body Weight and BMI: A Systematic Review and Meta-Analysis - Patsalos, Olivia; Dalton, Bethan; Leppanen, Jenni; Ibrahim, Mohammad A. A.; Himmerich, Hubertus (Frontiers in Pharmacology, 2020)
Objective The aim of this systematic review and meta-analysis of longitudinal studies was to ascertain to effects of TNF-α inhibitor therapy on body weight and BMI. Methods Three databases (PubMed, OVID, and EMBASE) were systematically searched from inception to August 2018. We identified prospective, retrospective, and randomized controlled studies in adults with immune-mediated inflammatory diseases treated with TNF-α inhibitors based on pre-specified inclusion criteria. A random-effects model was used to estimate standardised mean change (SMCC). Results Twenty-six longitudinal studies with a total of 1,245 participants were included in the meta-analysis. We found evidence for a small increase in body weight (SMCC = 0.24, p = .0006, 95% CI [0.10, 0.37]) and in BMI (SMCC = 0.26, p < .0001, 95% CI [0.13, 0.39]). On average, patients gained 0.90kg (SD = 5.13) under infliximab, 2.34kg (D = 5.65) under etanercept and 2.27kg (SD = 4.69) during treatment with adalimumab within the duration of the respective studies (4–104 weeks). Conclusion Our results yield further support the for the view that TNF-α inhibitors increase body weight and BMI as a potential side effect. Modulating cytokine signaling could be a future therapeutic mechanism to treat disorders associated with weight changes such as anorexia nervosa.